A Preoperative Retrobulbar Block in Patients Undergoing Scleral Buckling Reduces Pain, Endogenous Stress Response, and Improves Vigilance. Issue 6 (1st November 2003) - Vogt, Georg; Heiden, Michael; Lösche, Cay Christian; Lipfert, Peter
Abstract : Background and Objectives: This study aims to test postoperative analgesia by using retrobulbar block in patients with retinal detachment surgery. Methods: Twenty-nine patients scheduled for scleral buckling were included in this double-blind, randomized, prospective study. After induction of general anesthesia and opening of the conjunctiva, patients received either 4 mL bupivacaine 0.5% or 4 mL saline 0.9% injected into the retrobulbar space preoperatively. Heart rate and blood pressure were documented before the start of anesthesia, 10 and 50 minutes later, and 60 minutes after completion of surgery. At the same time points, 10 mL of blood were withdrawn for measurement of glucose and cortisol levels to evaluate the efficacy of retrobulbar block in eliminating humoral response. Postoperative scores for pain and vigilance were recorded 1, 6, and 24 hours after completion of surgery. The application of analgesic and antiemetic drugs was documented, as well as occurrence of nausea and vomiting. Results: A preoperative retrobulbar block in patients undergoing scleral buckling reduces pain, endogenous stress response, and improves vigilance. Conclusions: Because the analgesic effect of the retrobulbar block was considerably longer than pharmacologically expected, the combined retrobulbar and general anesthesia "protects" against postoperative pain and is recommended for patients undergoing scleral buckling.